2012
DOI: 10.1021/jz301250j
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Spin Dynamics in the Paramagnetic Endohedral Fullerene Gd3N@C80

Abstract: We acknowledge the support of the Hungarian National Research Fund OTKA NN76727, CNK80991, T72954, K107228, the New Hungary Development Plan TA ḾOP-4.2.1/B-09/1/KMR-2010-0002, and the Swiss NSF and its NCCR MaNEP. E .K. acknowledges support of the Bolyai Jańos Scholarship of the Hungarian Academy of Sciences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 21 publications
4
26
0
Order By: Relevance
“…Endohedral fullerenes present the added benefit of varying the composition of the encapsulated guest while maintaining the advantageous properties of the carbon π‐surface . These compounds have been explored as MRI contrast reagents, electron acceptors for photovoltaic cells, and single molecule magnets . Within the large family of endohedral fullerenes, metal nitride cluster fullerenes M 3 N@C 80 stand out due to their compositional diversity and relatively high synthetic yields .…”
Section: Figurementioning
confidence: 99%
“…Endohedral fullerenes present the added benefit of varying the composition of the encapsulated guest while maintaining the advantageous properties of the carbon π‐surface . These compounds have been explored as MRI contrast reagents, electron acceptors for photovoltaic cells, and single molecule magnets . Within the large family of endohedral fullerenes, metal nitride cluster fullerenes M 3 N@C 80 stand out due to their compositional diversity and relatively high synthetic yields .…”
Section: Figurementioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Recent discovery of single molecular magnetic behaviour in the Dy x Sc 3Àx N@C 80 -I h (x ¼ 1-3) series 12,19 calls for more detailed studies of NCF encapsulating lanthanide ions with large magnetic anisotropy.…”
Section: -5mentioning
confidence: 99%
“…Galili et al investigated the spin dynamics with the photoinduced intramolecular electron transfer in a parachute-shaped zinc porphyrin-fullerene dyad with time-resolved electron paramagnetic resonance [14]. Ná frá di et al studied the spin dynamics of Gd 3 N@C 80 with high-frequency electron spin resonance (ESR) and SQUID magnetometry and found the temperature-dependent magnetic property of Gd 3 N@C 80 [15]. Saffarzadeh and Kirczenow theoretically explored spindependent transport through Co@C 60 by using density functional and extended Hückel theories and found that very high degrees of spin polarization can be achieved for electrons tunneling through Co@C 60 dimers [16].…”
Section: Introductionmentioning
confidence: 99%